Environments of upper miocene sediments in the Hanoi depression interpreted from grain-size parameters - Tan, Mai Thanh; Thuan, Dinh Van; Dy, Nguyen Dich; Tao, Nguyen Van; Luong, Le Duc; Ha, Trinh Thi Thanh; Dao, Ngo Thi (Vietnam Journal of Earth Sciences, 2019)
The grain-size analysis is carried out for 49 samples of Upper Miocene sediments taken from three boreholes in the Hanoi depression. The statistic parameters of the grain size distributions such as percentiles, median, graphic mean, sorting or inclusive graphic standard deviation, inclusive graphic skewness, and graphic kurtosis are used to decipher the depositional environments and transportation mechanisms of sediments. Bivariate plotting of these parameters, the discriminant functions with four basic parameters of graphics mean, sorting, inclusive graphic skewness and graphic kurtosis, and the CM pattern with the one percentile (C) and median (M) diameters are applied for this determination. The plots of graphics mean versus sorting suggest 14% of samples being the sand sheet, 46% related to rivers and 40% of the estuarine environment. The sorting - inclusive graphic skewness plot shows a river-related environment for all samples. Linear discriminant functions show the sandstone of upper Miocene in Hanoi depression are deltaic sediments formed in unstably transporting and depositional environment, impacted by turbidity current in the coastal river-mouth. The CM pattern shows sediment transportation for most of the samples in three modes: rolling, suspension and rolling, and uniform suspension. The environmental dynamics are relatively complex and change over time.